2022
DOI: 10.3390/brainsci12070827
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Pathogenetic Pathways in Alzheimer’s Disease and Prediction of Potential Therapeutic Drugs

Abstract: Background. Alzheimer’s disease (AD) is a chronic and progressive neurodegenerative disease which affects more than 50 million patients and represents 60–80% of all cases of dementia. Mutations in the APP gene, mostly affecting the γ-secretase site of cleavage and presenilin mutations, have been identified in inherited forms of AD. Methods. In the present study, we performed a meta-analysis of the transcriptional signatures that characterize two familial AD mutations (APPV7171F and PSEN1M146V) in order to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Fexofenadine, also known as antihistamine, is a commonly used anti-allergy drug in clinical practice. In 2022, a meta-analysis by Petralia et al found that fexofenadine was one of ve drugs that might have a potential therapeutic effect on Alzheimer's disease [17] . Chloramphenicol is an antibiotic that acts on the 50S subunit of bacterial ribosomes, blocking protein synthesis and inhibiting both gram-positive and Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Fexofenadine, also known as antihistamine, is a commonly used anti-allergy drug in clinical practice. In 2022, a meta-analysis by Petralia et al found that fexofenadine was one of ve drugs that might have a potential therapeutic effect on Alzheimer's disease [17] . Chloramphenicol is an antibiotic that acts on the 50S subunit of bacterial ribosomes, blocking protein synthesis and inhibiting both gram-positive and Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The disease-oriented computational drug repurposing strategy that we present constitutes an accelerated alternative to costly drug development for AD as preliminary safety and bioavailability criteria are already established for the identified chemical compounds (Corbett et al, 2012; Mullen et al, 2016; Petralia et al, 2022). In 2021, approximately 40% of Alzheimer’s trials registered on ClinicalTrials.gov used repurposed existing medication (Cummings et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Dirithromycin itself has completed Phase 1 trials for healthy subjects treatment and was used to treat many types of bacterial infections. In the contrary, dirithromycin is a predicted drug predisposed to AD according to a study that uses transcriptional profiles and in silico method to predict potential therapeutic drugs and pathogenetic pathways for AD [22].…”
Section: Validation Of Drug Candidates By Literature Cross-referencingmentioning
confidence: 99%